2021
DOI: 10.3389/fped.2021.786638
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and Inattention in Young Patients Born With an Atrial Septal or Ventricular Septal Defect

Abstract: Background: Patients with congenital heart defects have a well-established risk of neuropsychiatric comorbidities. Inattention and hyperactivity are three to four times more frequent in children with complex congenital heart defects. We have previously shown a higher burden of overall attention deficit/hyperactivity disorder (ADHD) symptoms in adults with simple congenital heart defects as well. However, it is unknown whether the higher burden of ADHD symptoms is mainly driven by hyperactivity, inattention, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
3
7
1
Order By: Relevance
“…We have found the same pattern looking at adults with simple CHD where symptoms like inattention are difficult for a proxy to recognise. 6,52 This has also been found in a study investigating other chronic diseases in childhood. 53…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have found the same pattern looking at adults with simple CHD where symptoms like inattention are difficult for a proxy to recognise. 6,52 This has also been found in a study investigating other chronic diseases in childhood. 53…”
Section: Discussionsupporting
confidence: 71%
“…[2][3][4] In recent years, complex and simple CHD research has further revealed neurocognitive, social, and psychiatric difficulties. [5][6][7][8][9] Psychiatric disorders have a negative impact throughout life with a larger risk for lower educational attainments, unemployment, and divorce, [10][11][12] and early recognition and treatment may have the potential to change these negative impacts. However, studies investigating psychiatric co-morbidities in children and adolescents with CHD are sparse and show conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to ADHD symptoms, adolescents with TOF without or with a genetic diagnosis scored higher than referents on CADS ADHD Index ( P < .0001 for both). Lau-Jensen et al [22] investigate the distribution in ADHD symptoms in young adults with simple CHD. They reported 15% of all T-scores were above 65 In the CHD group to 4% of the T-scores in the control group and end up with patients with a simple CHDs have a higher symptom burden across all ADHD scores (ADHD—combined: P = .007, ADHD—inattention: P = .002, and ADHD—hyperactivity: P = .03) and all symptom sub-scores (inattention/memory problems: P = .001, hyperactivity/restlessness: P = .03, impulsivity/emotional lability: P = .001) therefore they emphasize the importance of the routine screening for ADHD symptoms to facilitate adequate help as these symptoms are easily overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Shillingford et al identified that the number of children with complex CHD receiving clinically significant scores for inattention and hyperactivity was 3–4 times higher than observed in the general population ( 11 ). Moreover, recent studies showed that patients with a simple CHD also have a higher ADHD symptom burden compared with population means and controls in adults ( 27 , 28 ). Therefore, ADHD-like symptoms has now become a common neurobehavioral and psychiatric disorder after congenital heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, half of the parents are unaware of ADHD-like symptoms and its harmfulness, only about one-fifth of parents sought special treatment, in particular, parents of children with isolated inattention symptoms were less likely to seek special help. Therefore, primary care clinicians and cardiac team should be alert to the early identification of ADHD-like symptoms in the children and adolescents with D-TGA after ASO during the follow-up, and provide them with appropriate medical treatments or interventions to improve their quality of life ( 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%